Effect of Ginger Tea on Chemotherapy-Induced Nausea and Vomiting among Patients Attending the Oncology Teaching Hospital, Baghdad 2020 - Remal Adel Kadhim; Besmah Mohammed Ali; Maysaa Adel Kadhim; Samer Jassim Mohammed (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Ginger has been widely used to relieve nausea and vomiting in several settings, one ofthem, patients receiving chemotherapy. This study was done to assess the effect of ginger in controlling thechemotherapy induced nausea and vomiting (CINV) among patients. Methods: An interventional (pre-post)study design was conducted in oncology teaching hospital in Baghdad for three months. Sixty participantswere randomly assigned into intervention group (30 participants received ginger tea (1.5 g/d) with routineantiemetic regimen for the first 5 days of the chemotherapy cycle) and control group (30 participants receivedonly routine antiemetic regimen). MASCC Antiemesis Tool (MAT) was used for assessment of CINV incancer patients before and after the use of ginger tea.Results: No significant difference was observed between the intervention and control groups in the acuteand delayed phases of CINV after intervention with ginger tea(p >0.05), but difference between the studygroups was found statistically significant (p <0.05)regarding the severity of nausea postchemotherapy.Conclusions: The addition of ginger tea to routine antiemetic regimen in patients receiving chemotherapyeffectively reduced the severity of nausea. However, there is no additional role for ginger in reducing theacute and delayed phases of CINV.